1980
DOI: 10.1007/bf00428107
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic ethanol treatment changes endorphin levels in brain and pituitary

Abstract: Acute ethanol administration increased methionine-enkephalin (met-enkephalin) and beta-endorphin levels in distinct areas of the rat brain, whereas chronically supplied ethanol caused a depression of met-enkephalin and beta-endorphin levels in most of the brain areas investigated. The beta-endorphin content of the intermediate/posterior lobe of the pituitary of rats and guinea pigs decreased by 70%. Withdrawal of ethanol resulted in a complete recovery of endorphin levels in brain and pituitary within two week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(52 citation statements)
references
References 19 publications
1
50
1
Order By: Relevance
“…The measures of GAL and DYN mRNA in the NAc revealed a pattern similar to ENK: a significant decline in low-ethanol drinkers with no change in the highethanol drinkers. While this result with DYN does not agree with evidence showing acute and chronic ethanol to stimulate DYN expression in the NAc (de Gortari et al, 2000;Li et al, 1998;Lindholm et al, 2000;Oswald and Wand, 2004;Seizinger et al, 1983;Schulz et al, 1980), this phenomenon in the NAc was very consistent, observed with each of the 3 peptides, in both the shell and core of the NAc, and only with the lower amount (1.0 g/kg/d) of ethanol consumed. Thus, in future investigations, it would be informative not only to examine possible differences between the forebrain and hypothalamic structures but also to vary the amounts of ethanol exposure.…”
Section: Effect Of Ethanol On Opioid Peptides In the Pvncontrasting
confidence: 83%
See 1 more Smart Citation
“…The measures of GAL and DYN mRNA in the NAc revealed a pattern similar to ENK: a significant decline in low-ethanol drinkers with no change in the highethanol drinkers. While this result with DYN does not agree with evidence showing acute and chronic ethanol to stimulate DYN expression in the NAc (de Gortari et al, 2000;Li et al, 1998;Lindholm et al, 2000;Oswald and Wand, 2004;Seizinger et al, 1983;Schulz et al, 1980), this phenomenon in the NAc was very consistent, observed with each of the 3 peptides, in both the shell and core of the NAc, and only with the lower amount (1.0 g/kg/d) of ethanol consumed. Thus, in future investigations, it would be informative not only to examine possible differences between the forebrain and hypothalamic structures but also to vary the amounts of ethanol exposure.…”
Section: Effect Of Ethanol On Opioid Peptides In the Pvncontrasting
confidence: 83%
“…Thus, mixed results have been obtained, with acute or chronic ethanol having no effect or causing either an increase or a decrease in levels, release, or expression of ENK, DYN, and b-endorphin in the hypothalamus Lawrence, 1999, 2001;de Gortari et al, 2000;Oswald and Wand, 2004;Patel and Pohorecky, 1989;Przewlocka and Lason, 1991;Schulz et al, 1980;Seizinger et al, 1983). To our knowledge, there are only 2 reports that have examined a specific hypothalamic nucleus, namely, the PVN.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that ethanol could regulate POMC peptide content in the brain as well as in the anterior and intermediate pituitary [11, 14, 17, 31 -33], However, studies on the effect of chronic ethanol treatment on hypothalamic ir|l-EP content have been in consistent, a decrease has been shown in some studies [31,34], while others failed to show changes [35,36], The discrepancy between different studies could be explained by the different routes or duration of ethanol administra tion, as well as the presence or absence of alcohol in the blood at the time of sacrifice. The results of the present investigations show no significant alteration in hypotha lamic ir|)-EP levels following chronic ethanol exposure in agreement with some of the previous studies [35,36].…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, since both control and ETOHtreated rats showed similar pituitary responsiveness to GRF, and because it is possible that an ETOH-induced elevation in SRIF would have caused a blunted response to GRF stimulation, it seems more likely that GRF secretion is most affected. However, since this cannot be decisively concluded from the present study, more research will be needed in this area to determine the interrelationships between ETOH, GRF, and SRIF, as well as on the multiple alterations that this drug can cause on neurotransmitters [12] and opioids [18] which, in turn, affect the secretion of these two neuropeptides.…”
Section: Discussionmentioning
confidence: 96%